Perbandingan Kinerja Protokol Routing HSR dan DSDV Pada Mobile Ad-Hoc Network (MANET) - Khalid Hamzah Haza Al Hamami; Primantara Hari Trisnawan; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Mobile ad hoc Network (MANET) is a portable autonomous node network equipped with a wireless interface, which communicates via a wireless connection without centralized administration. This network can self-configure and maintain network topology dynamically without infrastructure support. Because the mobile node's transmission range is limited, each node has a dependency on neighboring nodes to forward packets. Qualitative data analysis is performed on the performance of Hierarchical State Routing (HSR) and Destination-Sequenced Distance-Vector (DSDV) protocols by interpreting data from test results in the form of throughput, average jitter, average end to end delay, packet data delivery ratio, route overhead and route convergence time. This study uses Network Simulator 2.35 with node density scenarios using variations in the number of nodes totaling 50 nodes to 120 nodes with multiples of 10 nodes. The best value of parameters throughput, average jitter, average end to end delay, packet data delivery ratio and route overhead are 189.312 Kbps, 27.18 ms, 2798.04 ms, 18.93% and 230.25. These results were obtained in the DSDV routing protocol, so it can be concluded that the DSDV routing protocol has better performance than HSR on the node density aspect. A better convergence value is obtained by the DSDV protocol with an average convergence time of 0.028617977 seconds.